2022
DOI: 10.3390/molecules27206825
|View full text |Cite
|
Sign up to set email alerts
|

Process Optimization, Amino Acid Composition, and Antioxidant Activities of Protein and Polypeptide Extracted from Waste Beer Yeast

Abstract: Repurposing of waste beer yeast (WBY) that a main by-product of brewing industry has attracted considerable attention in recent years. In this study, the protein and polypeptide were extracted by ultrasonic-assisted extraction and enzymatic hydrolysis with process optimization, which resulted in a maximum yield of 73.94% and 61.24%, respectively. Both protein and polypeptide of WBY were composed of 17 Amino acids (AA) that included seven essential amino acids (EAA), and typically rich in glutamic acid (Glu) (6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 37 publications
0
0
0
Order By: Relevance
“…"Residual brewer's yeast is a brewing by-product that deserves considerable attention, due to the large amount produced. This by-product, once collected, can be marketed in the form of paste, powder, or even in liquid form" [24].…”
Section: Resultsmentioning
confidence: 99%
“…"Residual brewer's yeast is a brewing by-product that deserves considerable attention, due to the large amount produced. This by-product, once collected, can be marketed in the form of paste, powder, or even in liquid form" [24].…”
Section: Resultsmentioning
confidence: 99%
“…One study demonstrated that ultrasound-assisted enzymatic extraction (UAEE) effectively extracted 73.94% of water-soluble protein and 61.24% polypeptide from waste beer yeast [79]. This method proved more efficient and time-saving than traditional techniques, achieving higher protein yields compared to other sources: 39.12% from Moringa oleifera seeds [80] and only 8.5% of Ulva rigida macroalgae following alkaline pretreatment [81].…”
Section: Application Of Green Extraction Technologies For Fungal Prot...mentioning
confidence: 99%